2012
DOI: 10.1007/s11888-012-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Pathologist’s Role in Assessment of the Quality of the Mesorectum

Abstract: Total mesorectal excision (TME) is considered standard of care for rectal cancer treatment. Failure to remove the mesorectal fat envelope entirely may explain part of observed local and distant recurrences. Several studies suggest quality of the mesorectum after TME surgery as determined by pathological evaluation may influence prognosis. We aimed to determine the prognostic value of the plane of surgery as well as factors influencing the likelihood of a high-quality specimen by reviewing the literature. A poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 38 publications
5
59
0
2
Order By: Relevance
“…Seventeen of these patients (95 %) had a diverting loop ileostomy, and the time elapsed to the stoma closure was 19.9 weeks (range 1-49). The mean length of hospital stay was 9 days (range [7][8][9][10][11][12][13][14][15][16][17][18][19]. Histological analysis of the specimen revealed negative margins in all patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen of these patients (95 %) had a diverting loop ileostomy, and the time elapsed to the stoma closure was 19.9 weeks (range 1-49). The mean length of hospital stay was 9 days (range [7][8][9][10][11][12][13][14][15][16][17][18][19]. Histological analysis of the specimen revealed negative margins in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, functional and oncologic outcomes were found to be satisfactory. Furthermore, it is known [12] that the quality of mesorectal excision is an important factor related to incidence rate of local recurrence, regardless of the positive edge of the section. On the other hand, a demanding anatomical situation (narrow pelvis and/or a high BMI) may increase the difficulty of performing a proper TME [13,14], even in the case of laparoscopic resection [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesorectal integrity has been demonstrated to be one of the most important factors of both local and systemic tumor relapse, so it has been the priority objective throughout 37 . A meta-analysis of the quality of the specimen after open TME 38 showed the proportion of complete, nearly complete, and incomplete TME was 56.4%, 29.0%, and 14.6%, respectively, being the risk of local and overall recurrence associated with incomplete specimens. In the COLOR II trial 4 macroscopically complete resected specimens were recorded in 88% in the laparoscopic group and 92% in the open group.…”
Section: Discussionmentioning
confidence: 99%
“…Properly conducted TME reduces the recurrence rate to < 10% and increases overall 5-year survival to over 80% [4] . The Dutch TME trial [5] confirmed the above results, clearly stating an increased risk of local tumor recurrence for patients who had undergone a potentially curative procedure with incomplete mesorectal excision, as compared to patients in whom the specimen showed a completely resected mesorectum [6] . Laparoscopy offers better visualization of the pelvic cavity and therefore facilitates mobilization of the rectum [7] .…”
Section: Introductionmentioning
confidence: 72%